FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR (Studi Empiris Kantor Akuntan Publik Di Kota Semarang) - Amalia Yudhanti, 12.05.52.0157; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of audit structure, role conflict, role ambiguity, understanding of good governance, leadership style, cultural organizations, organizational commitment and the complexity of the tasks that directly affect the performance of the auditor in public accounting firm in the city of Semarang. The population in this study is the auditor who worked on a public accounting firm in the city of Semarang. Sampling was done by using purposive sampling method and the total sample of 79 respondents. Primary data collection method used is the questionnaire. Data were analyzed using multiple linear regression model. The results showed that the conflict of roles, understanding of good governance and leadership style not significant effect on the performance of auditors. While the audit structure, unclear roles, organizational culture, organizational commitment and the complexity of the task significant effect on the performance of auditors.Keywords: Audit Structure, Role Conflict, Role Ambiguity, Understanding Good Governance, Leadership Style, Organizational Culture, Organizational Commitment, Task Complexity and Performance Auditor